2020
DOI: 10.1101/2020.05.20.106930
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Complement C3-dependent glutamatergic synapse elimination in the developing hippocampus is region- and synapse-specific

Abstract: The complement cascade is an innate immune pathway that, in addition to host defense against pathogens, actively maintains tissue homeostasis. Complement is necessary for synaptic pruning during development and drives aberrant synapse loss in a number of neurodegenerative disorders that affect the hippocampus. However, the physiological function of complement in hippocampal synapse development is unknown. To address this, we investigated C3 -/mice at P16-18. We found that VGLUT2 + synapses were increased in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Nonetheless, the changes described were selective to CA3 but not CA1, although it was not associated with a loss of Homer + puncta, but instead VGLUT2+ puncta were preferentially reduced. This is supported by other observations of VGLUT2+ synapse specific pruning (Salter et al, 2020) albeit this was observed at PND 16-18 in the CA1 region, suggesting the CA1 region may undergo pruning earlier than CA3. These differences in pruning may be linked to known distinctions in microglial reactivity in subregions of the hippocampus (Vinet et al, 2012).…”
Section: Evidence For Complement-mediated Pruning In Other Brain Regi...supporting
confidence: 88%
“…Nonetheless, the changes described were selective to CA3 but not CA1, although it was not associated with a loss of Homer + puncta, but instead VGLUT2+ puncta were preferentially reduced. This is supported by other observations of VGLUT2+ synapse specific pruning (Salter et al, 2020) albeit this was observed at PND 16-18 in the CA1 region, suggesting the CA1 region may undergo pruning earlier than CA3. These differences in pruning may be linked to known distinctions in microglial reactivity in subregions of the hippocampus (Vinet et al, 2012).…”
Section: Evidence For Complement-mediated Pruning In Other Brain Regi...supporting
confidence: 88%
“…Microglial activation and phagocytosis of debris in the brain is in part mediated through the complement system via the activation of CR3 (CD11b/ CD18) through opsonized proteins such as iC3b (Borucki et al, 2020). Several laboratories have demonstrated that developmental elimination of VGlut2+ synapses can be mediated by this same complement-dependent pathway (Salter et al, 2020;Schafer et al, 2012;Stevens et al, 2007). NIF, a glycoprotein produced by a canine hookworm, is a selective antagonist of the CR3-CD11b subunit, preventing the recognition of its endogenous ligands (Rieu et al, 1994).…”
Section: Combined Prenatal Stressors Lead To An Increase In Functiona...mentioning
confidence: 99%
“…The C3 is one of the most abundant molecules of the complement system (Stephan et al, 2012). In the CSN, the complement system participates in synaptic pruning (Hua & Smith, 2004; Janeway Jr et al, 2001; Stephan et al, 2012), and in the hippocampus, C3 might be associated with the pruning of glutamatergic synapses (Perez‐Alcazar et al, 2014; Salter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%